The evolution of the Afrotemperate-endemic genus Macowania (Asteraceae) in the Drakensberg region of South Africa - Bentley, Joanne (Department of Biological Sciences, 2017)
The cosmopolitan Asteraceae tribe Gnaphalieae, or paper daisies or everlastings, form a significant component of both the dry and cool temperate floras of southern Africa. Within this tribe exists a small Afrotemperate genus, Macowania, endemic to the grassland biome of South Africa and occurring almost exclusively within the Drakensberg region, apart from two disjunct species in North Africa. The age, relationships and geographic origin of Macowania is investigated in order to provide insight into the factors affecting speciation, especially uplift events, on this small Afrotemperate genus. A well-supported phylogenetic hypothesis based on both nuclear and chloroplast genes suggests that Macowania is sister to a clade corresponding to the Relhania clade s.s., and that these are in turn sister to a clade containing the genera Athrixia and Pentatrichia. Macowania is monophyletic only with the inclusion of the enigmatic monotypic genus Arrowsmithia, resulting in the future synonymy of Macowania with Arrowsmithia. The anomalous species M. pinifolia, previously part of the genus Athrixia, is placed in a polytomy with the Relhania s.s. clade and the remaining species of Macowania and Arrowsmithia. DNA sequence data could not be obtained for several Macowania species, including the taxa from North Africa. The placement of these species within Macowania is confirmed by means of a parsimony analysis of morphological characters against a molecular backbone constraint tree. One species, M. tenuifolia, is well-supported in two different placements within Macowania by chloroplast and nuclear DNA sequence data. The best position of this species is inferred by incongruence decomposition analysis and morphological affinities. Bayesian relaxed clock methods and ancestral area reconstruction using maximum likelihood and squared change parsimony estimate the age and ancestral area of the genus, and determine the timing and route of colonisation of the Drakensberg. Diversification within Macowania is consistent in timing with the uplift events during the Miocene and Pliocene that resulted in significant vertical movement in eastern South Africa, suggesting that colonisation of the high-elevation Drakensberg grassland by Macowania was promoted by uplift. The topographic heterogeneity and increased river action resulting from the uplift may also have promoted evolution into new habitats and potentially mediated the movement of the ancestor of Macowania into the Drakensberg region via riparian habitats.